Pengembangan Perangkat Pembelajaran Kimia Berbasis Discovery Learning dengan Pendekatan Kontekstual pada Materi Larutan Penyangga - Nursyahraini, Nursyahraini; Sugiarti, Sugiarti; Sulastry, Taty (Chemistry Education Review (CER), 2020)
This study is development research, which aims at developing chemistry learning tools based on discovery learning with a contextual approach to the buffer solution which is valid, practical and effective. The development model employed in this study referred to 4D development model, which consisted of define, design, develop, and disseminate. The learning tools developed are RPP, LKPD, Student teaching materials, Media, and THB. The results of the study reveal that the learning tools based on discovery learning developed which had been validated indicates that the mean score is 3.58 which is in very valid criteria. The learning tools based on discovery learning is stated as practical and effective, because the results of the practically test reveal (1) the implementation of learning tools based on discovery learning is in the average of M = 1.74 in the category of (1.5 ≤ M ≤ 2.0) meaning that the aspects and criteria observed on the implementation of learning tools based on discovery learning is in entirely implemented category, (2) the teacher gave a very positive response on the learning tools based on discovery learning with the percentage of 91.61%, and (3) the students gave a very positive response on the learning tools based on discovery learning with the percentage of 87.36%. The learning tools is also met the criteria of effective with the following results that the learning outcomes has met effective criteria where the average score of 78.10 is obtained with the classical completeness 85.19. Therefore, the results of the study shows that the product of learning tools developed is categorized as valid, practical, and effective.